Errors in visual metacognition using cognitive illusions (2019)
The present research comprises five experiments that examine egocentric biases and metacognitive errors in visual metacognition. We used cognitive illusions/magic tricks as stimuli as they exploit counterintuitive limitations in cognition and metacognitive failures. The participants of these experiments were undergraduate students from the National University of Colombia and Goldsmiths, University of London. In Experiment 1, participants answered a general questionnaire about their ability to notice visual stimuli and changes. In Experiments 2-4, subjects watched magic tricks that exploit failures of visual awareness (i.e., inattentional blindness and change blindness) and made metacognitive judgments about themselves and about others. We also examined the level of surprise that participants reported at missing a visual change as surprise might be a tell-tale sign of underlying beliefs. Our findings suggest that participants' metacognitive judgments about themselves and about others were biased by prior beliefs and by their detection experiences. Specifically, subjects who detected how a magic trick was done made higher metacognitive judgments compared to those who experienced blindness, thus exhibiting an egocentric bias. Moreover, subjects made overestimation and underestimation errors. Interestingly, change blindness prevented participants from overestimating others’ ability to detect a visual change. Overall, these findings indicate that prior beliefs and the availability heuristic play a key role in making visual metacognitive judgments.